Computer vision and graphics : International Conference, ICCVG 2016, Warsaw, Poland, September 19-21, 2016, Proceedings /: International Conference, ICCVG 2016, Warsaw, Poland, September 19-21, 2016, Proceedings. (2016) - Unknown
No abstract available